(untitled) (Damascus University Journal of agriculture sciences, 2025)
This research was carried out at Cyano Research Station, Agricultural Scientific Research Center, Lattakia, General Authority for Scientific Agricultural Research, Syria during two successive seasons, 2020-2021 and 2021-2022 to study the effect of foliar spraying with paclobutrazol on growth of Yuma Citrange rootstock seedlings under salt stress conditions. The experiment was designed according to a split plots design. Five levels of NaCl salt (0, 8, 16, 24, 32 ms/cm) were applied, and five concentrations of paclobutrazol (0, 250, 500, 1000, 2000 ppm) were sprayed. The results showed that the gradual increase in salt levels resulted in a gradual decrease in all the studied indicators (morphological and physiological). Meanwhile, the treatment with paclobutrazol improved most of the studied parameters under all studied salinity levels. The interaction treatments of paclobutrazol (2000 ppm) and salinity (in all tested levels) showed superiority in root length (21.43 cm), shoots fresh and dry weight (23.71g, 11.17g, respectively), roots fresh and dry weight (25.16g, 8.18g, respectively), relative water content (58.88%), leaf content of chlorophyll a, b and carotenoids (0.66, 0.65 and 0.27 mg/g FW, respectively), proline accumulation (0.88 mg/g), leaves concentrations of nitrogen, phosphorus and potassium (4.65, 0.29, 1.09%, respectively) compared with interaction treatments of PBZ (o ppm) and salinity ( 17.30cm for root length, 14.56, 5.91g shoots fresh and dry weight, 15.91, 4.47g roots fresh and dry weight, 43.50% relative water content, 0.39, 0.37, 0.13 mg/g FW chlorophyll a, b and carotenoids, 0.64 mg/g proline and 3.22, 0.2, 0.87% NPK concentrations, respectively).